(3EOGQI GdeSJTajGJ (B/s - (3fUjQGJG, aQjO Jhajbs ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ hGdJhRjY(B, s, 2014)
(3jVe JGQjN GdeSJTajGJ hJWhQgG, GdEOGQI GdUMjI CgejJgG,eaghegG,hNUhUjJgG hGdeVGejf GdeJQJHI, GdeSJTai cLRA ef GdfXGe GdUMj hOhQg hhXGFag, fXGe GdeSJTai hechfGJg fXQI JMdjdjI, GdeSJTai hGdbGfhf hGdCNdGbjGJ, GdJNWjW dNOeGJ hHQGeL GdeSJTai, GdJNWjW GdGSJQGJjLj ddeSJTajGJ hGdGSJQGJjLjGJ GdfGLMI GdJWHjb, NWI GdehGRfI GdSfhjI ddeSJTai, EMUGFjGJ GdeSJTai hGdeDTQGJ GdGSJTaGFjI hOhQgG aj EOGQI GdeSJTai, JUeje Gdgjcd hGdJfXje GdOGNdj ddeSJTai, eOjQ GdeSJTai hGLHGJg hOhQg heSDhdjGJg, JfXje eLdS GdEOGQI, EOGQI hJfXje GdgjFI GdWHjI, EOGQI hJfXje NOeGJ GdeSJTai, GSJYeGdjI GdNOeGJ GdUMjI hGdESJTaGFjI, EOGQI JcdaI GdNOeI GdGSJTaGFjI, VHW GdYOhi aj GdeSJTajGJ, EOGQI LhOI GdQYGjI GdWHjI hGdLhOI GdTGedI aj GdeSJTajGJ, eYGjjQ hebGjjS Jbjje GdCOGA Gdcdj ddeSJTai hEOGQJg(B.s
(3GdeQGLY U(B.431s
Keywords: (3EOGQI GdeDSSGJs; (3GdeSJTajGJ(B- (3EOGQIs; (3Jbjje GdEOGA(B- (3eSJTajGJs